Acceptance of the Improvement on Mobile Application: A Study on User Engagement of a Highway Concessionary in Malaysia - Ishak, Aziza Isnoor; Ismail, Shahrinaz (Journal of Computing Technologies and Creative Content, 2017)
Challenges in the change of technology in recent years have affected highway concessionary companies in Malaysia. The change of direction in the company have put this research forward in looking at the aspect of user engagement via the usage of mobile application. It is proposed that the features in the current mobile application are to be improved in order to let the users, especially young drivers who are growing in numbers, feel more engaged to the services and management of the highway operations. Having said this, the objectives of this research are to gauge young drivers’ expectation on features in mobile application, and to analyse the acceptance of the prototype with the improved mobile application. Two surveys were conducted to meet these two objectives, both with respondents under the category of young drivers between the ages of 20 to 35. Better insight on what are desired by the respondents is found and presented in this paper, with suggestions on further improvement for future work.